Clinical Characteristics of Primary Vitreoretinal Lymphoma in an Indian Population. (3rd September 2017) - Mahajan, Sarakshi; Nijhawan, Raje; Rajwanshi, Aravind; Karkhur, Samendra; Mulkutar, Samyak; Dogra, Mohit; Lal, Vivek; Gupta, Vishali; Gupta, Amod
ABSTRACT: Purpose : Primary vitreoretinal lymphomas (PVRL) pose a major diagnostic challenge, especially in the countries with a high prevalence of infectious variety of uveitis. The present study aims to report the clinical characteristics and diagnostic difficulties in patients with PVRL in an Indian Population. Methods : Retrospective chart reviews of 12 patients with a diagnosis of PVRL. Results : The study included 6 men and 6 women, with a mean age of 55.66 ± 8.76 years. All had bilateral disease. The clinical signs included anterior uveitis (12 eyes; 50.0%); vitritis (18 eyes; 75%); vitreous clumps (16 eyes; 66.6%); subretinal deposits (11 eyes; 45.8%); retinal vasculitis (6 eyes; 25%); and optic disc swelling (2 eyes; 8.3%). The most commonly mistaken diagnosis was intraocular tuberculosis. The intraocular lesions responded to multiple intravitreal methotrexate injections. Conclusions : PVRL in India was likely to be mistaken for an infectious variety of uveitis. A high index of suspicion and thorough clinical examination is necessary to make the diagnosis.